Blended Learning of Indonesian Language Based on Merdeka Learning Independent Campus and Creative Economy - Yustinah Yustinah (Journal of Social Research, 2023)
Blended Learning Indonesian based on Merdeka-Belajar Kampus Merdeka-(MBKM) and Creative Economy at the Faculty of Economics, University of Muhammadiyah Semarang needs special attention. This is motivated by post-covid conditions—requiring student adaptation-- to an effective face-to-face learning situation. More than that, the advantages of blended learning are the latest effective learning solutions. This study aims to explain the implementation of lectures and evaluate Blended Learning Indonesian at the Faculty of Economics—majoring in Accounting and Management, University of Muhammadiyah Semarang. Blended Learning Indonesian be carried out through the stages of MBKM -- planning, implementing, and evaluating learning -- with creative economy content. These three stages are carried out to obtain maximum learning results. The subjects of the study were 254 fifth-semester Management students and first-semester Accounting students who were taking Indonesian courses. This study is descriptive statistical research. Data collection is carried out by filling in instruments using Google Forms. Data processing is carried out by comparing the percentage of the tendency of each student's answer. The results showed that Blended Learning Indonesian based on Merdeka Belajar Kampus Merdeka and Creative Economy at the Faculty of Economics, University of Muhammadiyah Semarang was implemented effectively. In the future, blended learning in Indonesian be an effective solution and a new breakthrough in independent learning.